The Effect of Processing Conditions on the Quality Characteristics of ‘Garri’ Produced from Cassava (Manihot esculenta) - Ogiehor, S. I.; Ikenebomeha, M. J. (Biological Sciences - PJSIR, 2006)
The effect of processing conditions, such as fermentation period, pH, and frying time and temperature on the microbiological, biochemical, physicochemical and organoleptic quality characteristics of ‘garri’ produced from cassava (Manihot esculenta) were evaluated. Results showed that the total bacterial count increased with the increase in fermen- tation period to 96 h up to 1.03 x 108, and thereafter decreased when the fermentation period was ended after 120 h. Mixed microbial populations of Bacillus, Streptococcus, Staphylococcus and Corynebacterium species dominated the early phase, while Leuconostoc, Lactobacillus, Candida, Geotrichun and Pichia species dominated the later phase of fermentation. The pH decreased from 5.04 ± 0.01 to 3.47 ± 0.02, while the titratable acidity at the end of the fermentation period increased from 0.01 ± 0.001 to 0.04 ± 0.001. With the exception of lipids, moisture and hydrocyanic acid contents, which decreased with fermentation period, the increase recorded in the carbohydrates, proteins, ash, and fibre contents were significant at p < 0.05. Frying at 75.5 ± 0.5 °C for 20 min drastically reduced the bioload by several folds. Sharp reductions, which were significant at p < 0.001, 0.01, 0.05, were recorded in the moisture and hydrocyanic acid contents. Different stages of processing impacted significant effects on the sensory attributes evaluated. The recorded observations are likely to be useful for developing viable indices for the production, processing and handling of ‘garri’.